Losartan Attenuates Degradation of Aorta and Lung Tissue Micromechanics in a Mouse Model of Severe Marfan Syndrome - Lee, Jia-Jye (Ann Biomed Eng, 2016)
Marfan syndrome (MFS) is an autosomal dominant disease of the connective tissue due to mutations in the fibrillin-1 gene (FBN1). This study aimed at characterizing microelastic properties of the ascending aorta wall and lung parenchyma tissues from wild type (WT) and age-matched Fbn1 hypomorphic mice (Fbn1(mgR/mgR) mice) to identify tissue-specific biomechanical effects of aging and disease in MFS. Atomic force microscopy (AFM) was used to indent lung parenchyma and aortic wall tissues, using Hybrid Eshelby Decomposition analysis to extract layer-specific properties of the intima and media. The intima stiffened with age and was not different between WT and Fbn1(mgR/mgR) tissues, whereas the media layer of mutant aortas showed progressive structural and mechanical degradation with a modulus that was 50% softer than WT by 3.5 months of age. Similarly, mutant mice displayed progressive structural and mechanical deterioration of lung tissue, which was over 85% softer than WT by 3.5 months of age. Chronic treatment with the angiotensin type I receptor antagonist, losartan, attenuated the aorta and lung tissue degradation, resulting in structural and mechanical properties not significantly different from age-matched WT controls. By revealing micromechanical softening of elastin-rich aorta and lung tissues with disease progression in fibrillin-1 deficient mice, our findings support the use of losartan as a prophylactic treatment that may abrogate the life-threatening symptoms of MFS.